Cortisol before extinction generalization alters its neural correlates during retrieval processes. (September 2021) - Hagedorn, B.; Wolf, O.T.; Merz, C.J.
Abstract : Background: One suggested candidate for enhancing and generalizing extinction learning is the administration of the stress hormone cortisol prior to extinction learning. Methods: In this study (https://osf.io/zwhx8 ), we aimed to create a generalized extinction memory trace in 60 healthy men and women using multiple sizes of one conditioned stimulus (CS+G; generalized) during extinction training, whereas the other CS was presented in its original size (CS+N; non-generalized). Extinction training took place after pharmacological administration of the human stress hormone cortisol or placebo. Results: Prolonged fear activation occurred for CS+G minus CS+N during extinction training, whereas cortisol-modulated hippocampal activation was observed during retrieval. Amygdala and dACC responding during reinstatement test were reduced for the CS+G as compared to CS+N. However, cortisol abolished this dACC activation relative to placebo. Conclusion: Extinction generalization processes appear to rely on prolonged fear expression that in turn leads to attenuated return of fear after reinstatement. Cortisol administration prior to extinction training, however, appears to selectively enhance consolidation for the standard extinction stimulus.